Methicillin-Resistant Staphylococcus Aureus infection exacerbates NSCLC cell metastasis by up-regulating TLR4/MyD88 pathway - An, J; Li, Z; Dong, Y; Ren, J; Guo, K (Cellular and Molecular Biology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) infection is a major public health problem worldwide, which brings to a more great threat for cancer patients. It’s necessary to give attentions to lung cancer combined with MRSA. This study mainly focuses on the influences of MRSA on lung cancer cells (A549). We first found that MRSA infection can enhance metastasis ability of A549 cell and increase matrix metalloproteinase (MMP2 and MMP9) expressions in MRSA-infected A549 cell. Toll-like receptors (TLRs) have been reported to play an important role in tumor cell initiation and migration, and regulate the expression of MMPs in tumors. Our further research indicates that Toll-like receptor 4 (TLR4)/molecules myeloid differentiation factor 88 (MyD88) signaling was up-regulated in MRSA-infected A549 cell. After silencing TLR4 or MyD88 gene, the enhanced metastasis ability of A549 cell by MRSA was decreased significantly; Also, MMP2 and MMP9 expression increase was reversed. In conclusion, MRSA infection can enhance NSCLC cell metastasis by up-regulating TLR4/MyD88 signaling.